Effectiveness of Electroconvulsive Therapy in Patients With Major Depressive Disorder and Comorbid Borderline Personality Disorder. Issue 1 (March 2019) - Lee, James H.; Kung, Simon; Rasmussen, Keith G.; Palmer, Brian A.
Abstract : Objective: Previous research suggests that electroconvulsive therapy (ECT)—the criterion standard for the treatment of severe depression—is not as effective when the patient has comorbid borderline personality disorder (BPD). The ECT outcomes of patients with and without BPD were compared in a retrospective chart review to test this claim. Methods: We enrolled 137 patients with a diagnosis of major depressive disorder who completed the McLean Screening Instrument for Borderline Personality Disorder. Twenty-nine patients had positive screening scores for BPD. The difference in Patient Health Questionnaire (PHQ-9) scores before and after ECT was compared between patients with and without BPD. Follow-up PHQ-9 scores determined after treatment were collected and analyzed. Results: Electroconvulsive therapy equally improved symptoms of depression as measured by PHQ-9 score in both patients who screened positive and patients who screened negative for BPD. No difference in the increase in PHQ-9 scores between these 2 groups was noted 1 month after treatment ( P = 0.19). Conclusions: These data showed that a positive BPD screen does not necessarily predict a poorer response to ECT, nor does it predict greater symptom recurrence after ECT. This does not suggest that ECT is necessarily an appropriate treatment for major depressive disorder in patients with a comorbid BPD, given the limitations of screening instruments.